2017
DOI: 10.3390/ijms18040794
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide A Ameliorates LPS-Induced Inflammatory Responses In Vitro and In Vivo

Abstract: Ginkgolide A (GA) is a natural compound isolated from Ginkgo biloba and has been used to treat cardiovascular diseases and diabetic vascular complications. However, only a few studies have been conducted on the anti-inflammatory effects of GA. In particular, no related reports have been published in a common inflammation model of lipopolysaccharide (LPS)-stimulated macrophages, and the anti-inflammatory mechanisms of GA have not been fully elucidated. In the present study, we extensively investigated the anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Li et al () assayed ginkgolide A, as an active ingredient of GBLE. This compound attenuated the expression of proinflammatory mediators, such as COX‐2 and NO as well as proinflammatory cytokines, including TNF‐α, IL‐6, and IL‐1 in mouse peritoneal macrophages, mouse macrophage RAW264.7 cells, and differentiated human monocytes, which all cell types were intoxicated by LPS in vitro.…”
Section: Natural Toxinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al () assayed ginkgolide A, as an active ingredient of GBLE. This compound attenuated the expression of proinflammatory mediators, such as COX‐2 and NO as well as proinflammatory cytokines, including TNF‐α, IL‐6, and IL‐1 in mouse peritoneal macrophages, mouse macrophage RAW264.7 cells, and differentiated human monocytes, which all cell types were intoxicated by LPS in vitro.…”
Section: Natural Toxinsmentioning
confidence: 99%
“…These effects were partially attributed to the down regulation of NF‐κB, P38 MAPK, and activation of AMPK signalling pathways. Moreover, ginkgolide A was able to inhibit the release of TNF‐α and IL‐6 induced by LPS in mice (Li et al, ). As it is reported above, the results obtained from the in vitro study on inflammatory cells support the outcomes of the in vivo research projects.…”
Section: Natural Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the anti‐inflammatory activity of Ginkgo , previous studies have shown that the standard G. biloba leaf extract (EGb761) can modulate inflammatory mediators and cytokines to suppress inflammation in vitro and in vivo, and the main active components of EGb761, total ginkgo flavonoid O ‐glycosides, can also inhibit lipopolysaccharide (LPS)‐induced nitric oxide (NO) release in RAW264.7 macrophages (Zhang et al, ). Among the active compounds, Ginkgolide A was reported to ameliorate inflammatory responses induced by LPS in vitro and in vivo (Li et al, ). Ginkgolide B also possesses anti‐inflammatory effects (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulated by LPS, RAW264.7 macrophages can secrete various inflammatory mediators, such as NO, iNOS, PGE 2 , and COX‐2, and inflammatory cytokines, such as TNF‐α and IL‐6. The elevation of inflammatory mediator and cytokine levels is closely associated with the development of inflammatory diseases (Li et al, ). Therefore, screening the agents that can suppress inflammatory mediators and cytokines is essential for developing new anti‐inflammatory drugs (Yoon, Kim, Lee, Kim, & Oh, ).…”
Section: Introductionmentioning
confidence: 99%